Academic Researches on Fazlur Rahman: An Assessment - Juneefa Bilal (Analisa: Journal of Social Science and Religion, 2021)
Fazlur Rahman (1919-1988), a liberal and modernist thinker of the twentieth century, was an influential scholar from Pakistan. He was a notable scholar of Islamic philosophy and was a prolific writer. Without any exaggeration, it can be asserted that Fazlur Rahman produced such a revolutionary and marvelous literature which made his thought a fascinating subject for research and analysis. Throughout the Globe, attempts have been made to conduct researches in order to assess his contribution in the varied disciplines of Islamic scholarship. This has continued in the last century and is continuing in the present century as well. Numerous researches have been carried-out on different aspects and dimensions of Fazlur Rahman’s thought and contribution. In this backdrop, this paper anticipates to present an appraisal and assessment of those academic researchers in order to gain acquaintance of the varied dimensions of Fazlur Rahman’s religious thought. This paper is qualitative in nature and in order to assess the academic works done on Fazlur Rahman, a descriptive and explanatory-cum-analytical approach was followed. This review paper will help in apprehending the different approaches and methodologies employed by different scholars in understanding the multi-dimensional aspects of Fazlur Rahman’s religious thought and provide an assessment of his contribution in different realms of Islamic scholarship